A descriptive survey of the Filipino context in art deco ornamentations and art motifs in the Metropolitan Theater - Rodrigo, Edwin C.
The descriptive survey determined the Filipino context in Art Deco ornamentations and art motifs found in the Metropolitan Theater. The specific objectives of the study identified the Art Deco ornamentations and art motifs in the Metropolitan Theater that are reflective of the Filipino way of life. The distinctiveness of the Filipino Art Deco Style also became a major consideration of the study. The researcher used a purposive sampling wherein an American colonial Art Deco structure in Manila, the Metropolitan Theater, became the study site. Its distinctive architectural and historical significance became the main criteria for the choice. The survey focused on the structure's facade as a representative sample because of its architectural and decorative ornamentations. Data gathering consisted of photographic documentation and ocular observation. The data collected were first classified quantitatively by tabulation, categorization and data organization using a content analysis format. The elements of Filipino Architectural Expression were used as categories to identify the Art Deco ornamentations and art motifs and distinctiveness in the Filipino context. These elements include localized flora and fauna motifs; influences from other Asian cultures; eclecticism due to western art and architecture influences; human scale with reference to Filipino anthropometrics; and use of local materials. Frequency and occurrence of the identified elements show that the ornamentations were expressed following three major design influences: local adaptation, regional or neighboring Asian cultures, and western art and architecture movements. These influences were adapted and used in the Art Deco Style. A major finding of the study articulates the ways these influences were consistently assimilated to the forms through time as a distinct local Art Deco style development. The ornamentations and decorative motifs of the Metropolitan Theater showed a fusion of local and foreign influences. These influences were adapted and modified to fit they way of life of the Filipino people wherein local floral and foliage patterns were used extensively in the decorations. The study can be used as a reference for the stylistic documentation of heritage structure providing a possible set of guidelines on historical stylistic documentation.